Strategies of peace - Philpott, Daniel, 1967-; Powers, Gerard F. (New York ; Oxford : Oxford University Press, 2010)
Scholars of peacebuilding rethink the basic goals & methods of conflict resolution and argue for a holistic approach that they term strategic peacebuilding, which aims not only for stability but for a comprehensive solution that incorporates apology, forgiveness reconciliation, & most crucially, religion.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Peace-building.